2001
DOI: 10.1128/iai.69.2.912-916.2001
|View full text |Cite
|
Sign up to set email alerts
|

Initial Characterization of the Hemolysin Stachylysin fromStachybotrys chartarum

Abstract: Stachybotrys chartarum is a toxigenic fungus that has been associated with human health concerns, including pulmonary hemorrhage and hemosiderosis. This fungus produces a hemolysin, stachylysin, which in its apparent monomeric form has a molecular mass of 11,920 Da as determined by matrix-assisted laser desorption ionization-time of flight mass spectrometry. However, it appears to form polydispersed aggregates, which confounds understanding of the actual hemolytically active form. Exhaustive dialysis or heat t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
47
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(49 citation statements)
references
References 26 publications
2
47
0
Order By: Relevance
“…So far, all of these hemolysins demonstrate a characteristic response on SBA-that is, there is initial darkening of the SBA medium beyond the colony. This darkened area turns bluish green and then clears over 24 to 48 h (Van Emon et al, 2003;Vesper et al, 2001). (This is similar to the slow reaction described by Luo et al [2001] for the Candida hemolysins.)…”
Section: Filamentous Fungisupporting
confidence: 55%
See 3 more Smart Citations
“…So far, all of these hemolysins demonstrate a characteristic response on SBA-that is, there is initial darkening of the SBA medium beyond the colony. This darkened area turns bluish green and then clears over 24 to 48 h (Van Emon et al, 2003;Vesper et al, 2001). (This is similar to the slow reaction described by Luo et al [2001] for the Candida hemolysins.)…”
Section: Filamentous Fungisupporting
confidence: 55%
“…We showed that stachylysin caused pores in sheep 200 VESPER AND VESPER RBC membranes (Vesper et al, 2001), but L. terrestis has no oxygencarrying cells and a closed vascular system. The release of erythrocruorin hemoglobin from L. terrestis and the development of aneurism-like structures suggested that stachylysin caused cytolytic vascular leakage, resulting in an LD 50 of 1100 g/Kg in L. terrestis (Vesper and Vesper, 2002).…”
Section: Stachylysinmentioning
confidence: 99%
See 2 more Smart Citations
“…2,3 After incubation, the coated plates w ere washed three times with phosphate-buffered saline-0.05% Tween 20 (PBST, Sigma). Standards of 11 different concentrations of stachy lysin-BSA (0 to 62.5 ng/ml) diluted in 1: 20 diluted (PBST) commercially available human sera o r diluted (1:20 in PBS T) subject sera (in triplicate) were mixed with affinit y-purified rabbit antistachylysin IgG ( Bethyl Larboratories, Montgomery, TX) diluted 1:20,000 in PBST) in test tubes and incubated at 4°C for 2 4 hours.…”
Section: Stachylysin™ Assaymentioning
confidence: 99%